Impacts of electric vehicles on power system load profile - Pyae, Ko Ko (Nanyang Technological University, 2022)
One of the largest sources producing greenhouses gases in the world is the internal combustion engine vehicles (ICE). In Singapore, the vehicle population is close to a million, majority of which are using ICEs. ICEs produce harmful gases that cause global warming. As a result, the atmospheric temperature on earth is increasing drastically, causing climatic changes and affecting existing eco-systems. The Singapore government has plans to adopt 100 percent electric vehicles (EVs) by 2040 to build up a greener mobility transport infrastructure. Electric vehicles bring about environmental benefits, such as having no exhaust pipes to emit any pollutants, and the ability to be charged by using other renewable sources such as solar energy or wind turbine energy. To facilitate the adoption of a fully green fleet in any country, research and considerations of many factors has to be done as the increasing volume of EVs that use local electrical power might have a significant impact to the existing power grid in long run. Without an active grid operator or monitoring system, EVs charging systems may cause more harm than benefits to local power grids if they are not regulated. This paper aims to research and analyse power system load profiles that are affected at the distribution level, its main focus being the regulation of voltage variations, load demand and active power losses. The paper will also feature case studies where high volume of EVs charging may cause issues with voltage stability and reliability mainly due to load change and discuss methods to alleviate such incidents from happening within the power system.